Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1074/jbc.274.13.8694
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel, Non-peptidyl Antagonist of the Human Glucagon Receptor

Abstract: Glucagon is a 29-amino acid peptide that is an important counter-regulatory hormone in the control of glucose homeostasis (1). Glucagon secretion from the endocrine pancreas induces an increase in hepatic glycogenolysis and gluconeogenesis, and it attenuates the ability of insulin to inhibit these processes. As such, the overall rates of hepatic glucose synthesis and glycogen metabolism are controlled by the systemic ratio of insulin and glucagon (2, 3). Therefore, glucagon antagonists have the potential to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
80
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 12 publications
3
80
0
Order By: Relevance
“…Many of the identified small-molecule agonists were discovered through random or directed functional highthroughput screening of large chemical libraries, which also would identify agonists that do not necessarily bind to the peptide-binding site, the orthosteric site. Peptides are thought to bind to the extracellular portion of the receptor, whereas small molecules may bind more deeply in the transmembrane region (31,32). Several GPCR agonists that affect the receptor response to the natural ligands via a noncompetitive site or allosteric site have during recent years been found for receptor families A and C, but so far not for family B.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the identified small-molecule agonists were discovered through random or directed functional highthroughput screening of large chemical libraries, which also would identify agonists that do not necessarily bind to the peptide-binding site, the orthosteric site. Peptides are thought to bind to the extracellular portion of the receptor, whereas small molecules may bind more deeply in the transmembrane region (31,32). Several GPCR agonists that affect the receptor response to the natural ligands via a noncompetitive site or allosteric site have during recent years been found for receptor families A and C, but so far not for family B.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no small-molecule agonists have been described in the B family. Small-molecule antagonists have been described for two members of this family, the glucagon receptor and the CRF receptor (27)(28)(29). The GLP-1 peptide and several of the other peptide hormone ligands in this receptor family do not have a well defined secondary structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chinese hamster ovary (CHO) cells expressing the cloned human GCGR (CHO-hGCGR) have been previously described (20,21). The CHO-hGIPR cell line was produced by transfecting human glucose insulinotropic peptide receptor (hGIPR) cDNA (kindly provided by T. Usdin, National Institutes of Health, Bethesda, MD) into CHO cells.…”
Section: Methodsmentioning
confidence: 99%
“…Selective antagonists L168049 (Cascieri et al, 1999), des-His 1 -[Glu 9 ]glucagon amide (Post et al, 1993), BAY27-9955 (Petersen and Sullivan, 2001), xNNC92-1687 (Madsen et al, 1998) Exendin-(9-39) (Thorens et al, 1993) (Schally and Varga, 1999), JV-1-38 (Schally and Varga, 1999) [(CH2NH) 4,5 ]secretin (Kim et al, 1993) The glucagon receptor has been reported to interact with receptor activity modifying proteins (RAMPs), specifically RAMP2, in heterologous expression systems (Christopoulos et al, 2003), although the physiological significance of this has yet to be established. …”
Section: Ensembl Id Ensg00000121853mentioning
confidence: 99%